Solid electrolyte membrane and preparation method and application thereof

By modifying the graft active functional groups on the surface of the substrate of the solid electrolyte membrane to form a crosslinking network, the problems of weak strength and structural instability of the solid electrolyte membrane are solved, higher mechanical strength and structural stability are achieved, and the energy density and safety of the battery are improved.

CN119674197AActive Publication Date: 2025-03-21GUOLIAN CORE MATERIALS (BEIJING) TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411684987.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-21
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The weak strength and unstable structure of the existing solid electrolyte membranes lead to cracks or breakages during charging and discharging of batteries, affecting the energy density and safety of the batteries.

Method used

By modifying the surface of the substrate (such as non-woven fabric) to form a crosslinking network with the adhesive in the solid electrolyte membrane, the strength and structural stability of the electrolyte membrane are enhanced.

Benefits of technology

It improves the mechanical strength and structural stability of the solid electrolyte membrane, avoids cracks or breakage problems during the charging and discharging process of the battery, and improves the energy density and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674197A_ABST
    Figure CN119674197A_ABST
Patent Text Reader

Abstract

The invention provides a solid electrolyte membrane and a preparation method and application thereof. The solid electrolyte membrane provided by the invention comprises an electrolyte layer and a base material layer, the electrolyte layer comprises a solid electrolyte material and a binder, the base material layer is grafted with one or two or more active functional groups through surface modification treatment, and the active functional groups can be polymerized with the binder to form a cross-linked network; and the binder is an unsaturated binder. According to the solid electrolyte membrane provided by the invention, the electrolyte layer and the base material layer are connected through the cross-linked network formed by polymerization of the active functional group and the binder, so that the strength and the structural stability are improved, and the problem that the base material is easy to fall off because the base material is only in single-sided contact with the electrolyte layer is avoided; the electronic conductivity of the electrolyte membrane can be reduced, and the self-discharge phenomenon can be effectively inhibited. According to the preparation method provided by the invention, the electrolyte layer forms a film independently, large-scale roll-to-roll process production is easier to realize, and the preparation method can be used for a high-energy-density solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a solid-state electrolyte membrane and a preparation method and application thereof. Background Art

[0002] All-solid-state batteries, which use solid electrolytes instead of traditional liquid electrolytes, have high energy density, high power density and high safety. They are expected to meet the needs of more life scenarios and are considered to be a key direction for future industry development.

[0003] Among the solid electrolytes that have been developed, sulfide solid electrolytes have the highest ion conductivity, which has exceeded the level of commercial electrolytes and has received increasing attention in recent years. The sulfide solid electrolyte layer formed by dry powder pressing is extremely brittle. During the battery charging and discharging process, the electrolyte layer is prone to cracks or even breakage. In order to avoid battery failure caused by the above problems, the thickness of the pressed layer is usually 0.8-1.2mm, but this is not conducive to industrialization, and it also greatly reduces the mass fraction of active substances in the battery system, resulting in a low energy density of the battery.

[0004] To this end, the sulfide electrolyte needs to be prepared into a membrane. Currently, the preparation methods of solid electrolyte membranes are mainly divided into dry method and wet method. The wet method is to add a binder and an electrolyte to a solvent to form a slurry, and then apply and dry it to form a membrane. This method has poor mechanical strength after the membrane is formed, is brittle and easy to fall off, and has a low yield rate. Summary of the invention

[0005] In order to solve the problems of weak strength and unstable structure of the solid electrolyte membrane in the above prior art, the present invention provides a solid electrolyte membrane, which enhances the strength and structural stability of the electrolyte membrane by modifying the surface of a substrate (such as a non-woven fabric) and grafting active functional groups through a cross-linked network generated by the substrate and a binder in the solid electrolyte membrane.

[0006] The first object of the present invention is to provide a solid electrolyte membrane, comprising an electrolyte layer and a substrate layer, wherein the electrolyte layer comprises a solid electrolyte material and a binder, and the substrate layer is surface-modified and grafted with at least one active functional group, and the active functional group can polymerize with the binder to form a cross-linked network; the binder is an unsaturated binder.

[0007] In some embodiments of the present invention, the active functional group can be selected from at least one of -OH, -CO-, -COOH, -CO, and -NH2.

[0008] In some embodiments of the present invention, the binder is selected from one or two or more of butadiene rubber, styrene butadiene rubber (SBR), nitrile rubber (NBR), and styrene-butadiene-styrene block copolymer (SBS).

[0009] The substrate is surface-modified and grafted with a variety of active functional groups, which can polymerize with the unsaturated bonds (such as double bonds) on the binder to form a cross-linked network, thereby enhancing the chemical bonding between the substrate and the electrolyte membrane and increasing the roughness and shear strength of the substrate surface, thereby preparing an electrolyte membrane with a compact structure and not easy to fall off, such as a sulfide electrolyte membrane.

[0010] In some embodiments of the present invention, the amount of the binder added is 1-10 wt %, preferably 1-5 wt %, of the amount of the electrolyte material used.

[0011] In some embodiments of the present invention, the surface modification treatment is selected from at least one of plasma treatment, ozone treatment, chemical reagent oxidation, high-energy radiation treatment, and corona discharge treatment; preferably, the surface modification treatment is selected from plasma treatment and / or ozone treatment.

[0012] In some embodiments of the present invention, the electrolyte layer includes a first electrolyte layer and a second electrolyte layer, and the substrate layer is located between the first electrolyte layer and the second electrolyte layer or close to the pole piece. In the solid electrolyte membrane provided by the present invention, the substrate layer is located between the first electrolyte layer and the second electrolyte layer or close to the pole piece, thereby avoiding the problem that the substrate is only in contact with one side of the electrolyte layer and is easy to fall off.

[0013] In some embodiments of the present invention, the substrate layer is selected from at least one of ceramics and non-woven fabrics.

[0014] In some embodiments of the present invention, the non-woven fabric is selected from at least one of polypropylene (PP), polyester (PET), nylon (PA), acrylic, polyethylene-vinyl acetate (PEVA), ethylene (HDPE) and vinyl (PVC); preferably, the non-woven fabric web layer includes at least one of polyester (PET), nylon (PA), polyethylene-vinyl acetate (PEVA) and vinyl (PVC).

[0015] In some embodiments of the present invention, the non-woven fabric includes non-woven fibers, and the non-woven fibers are distributed in an irregular manner; preferably, the non-woven fibers are selected from at least one of meltblown non-woven fibers, cross non-woven fibers, random non-woven fibers, spun non-woven fibers, needle-punched non-woven fibers, ruptured fiber non-woven fibers, and tow open fiber non-woven fibers.

[0016] In some embodiments of the present invention, the non-woven fabric fibers form a network structure; preferably, the network structure is at least one of a sheet or a web formed by friction, entanglement or bonding.

[0017] In some embodiments of the present invention, the sheet or fiber mesh is parallel to the electrolyte layer; the sheet or fiber mesh can reduce the electronic conductivity of the electrolyte membrane, and can effectively suppress the self-discharge phenomenon. The independently filmed electrolyte layer is easier to achieve large-scale roll-to-roll production and can be used for high energy density solid-state batteries.

[0018] If the porosity of the sheet or fiber mesh is too low, it will easily lead to an increase in internal resistance and have a greater impact on ionic conductivity; if the porosity is too high, the mechanical strength of the support will decrease. Therefore, in the present invention, the surface porosity of the sheet or fiber mesh can be controlled at 35%-95%; in some embodiments, the surface porosity of the sheet or fiber mesh can also be controlled at 75%-80%. The solid electrolyte membrane has high mechanical strength and low internal resistance, and a good balance is achieved between the two.

[0019] In some embodiments of the present invention, the thickness of the non-woven fabric may be 5 μm-100 μm; in some embodiments, the thickness of the non-woven fabric may also be 8 μm-16 μm.

[0020] The electrolyte slurry includes an electrolyte material, a binder and a solvent. In some embodiments of the present invention, the solid electrolyte material can be at least one of an oxide electrolyte, a polymer electrolyte and a sulfide electrolyte, preferably a sulfide electrolyte with the highest ion conductivity.

[0021] In some embodiments of the present invention, the sulfide electrolyte includes Li2S-P2S5, Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 5.5 PS 4.5 C l1.5 At least one of .

[0022] In some embodiments of the present invention, the particle size range of the powder of the sulfide electrolyte can be controlled within 1-10 μm. Preferably, the particle size range of the powder of the sulfide electrolyte is controlled within 1-3 μm.

[0023] In some embodiments of the present invention, the solvent includes one or more of toluene, xylene, anisole, butyl butyrate, n-heptane, pentane, hexane, octane, cyclohexane, cyclohexanone, toluene cyclohexanone, chlorobenzene, dichlorobenzene, dichloromethane, methanol, ethanol, isopropanol, ether, propylene oxide, methyl acetate, ethyl acetate, propyl acetate, acetone, methyl butyl ketone, methyl isobutyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and acetonitrile; preferably, the solvent for dispersing the sulfide electrolyte includes one or two or more of toluene, xylene, anisole, and n-heptane.

[0024] As a second aspect of the present invention, a method for preparing the aforementioned solid electrolyte membrane is provided, comprising: subjecting a substrate to surface modification treatment to obtain a surface-modified substrate; preparing an electrolyte slurry and coating the electrolyte slurry.

[0025] In the prior art, the non-woven fabric / substrate layer is first fixed, and then the slurry is evenly coated on the non-woven fabric / substrate layer at one time, and then dried to form a film. The corresponding electrolyte membrane, whose non-woven fabric / substrate is only in single-sided contact with the electrolyte layer or the actual contact area is insufficient, is prone to fall off, or the position of the substrate in the electrolyte layer cannot be controlled. In order to solve this technical problem, and as a further preferred embodiment of the electrolyte membrane preparation method of the present invention, the present invention adopts a layered coating method to coat the electrolyte slurry. The specific operation is: first, a part of the electrolyte slurry is coated on the current collector or PET film, and preliminarily dried to obtain the first electrolyte layer. Before the first electrolyte layer is completely dry, a layer of the surface modified substrate (such as non-woven fabric) is placed, and then the remaining slurry is coated on the surface modified substrate to obtain the second electrolyte layer. By applying the electrolyte slurry in layers, the position of the substrate or the sheet or fiber mesh in the electrolyte layer can be controlled, such as being placed in the middle of the first and second electrolyte layers or close to the electrode side. By doing so, the problem of the substrate easily falling off due to only contacting the electrolyte layer on one side or insufficient actual contact area can be avoided. The resulting electrolyte membrane has a compact structure, is less prone to falling off, and is more solid.

[0026] The above-mentioned solid electrolyte membrane can be applied to solid-state batteries. Therefore, as a third aspect of the present invention, a solid-state battery is provided, which uses the above-mentioned solid electrolyte membrane or the solid electrolyte membrane obtained by the above-mentioned preparation method.

[0027] As a fourth aspect of the present invention, there is provided an electrical device which employs the aforementioned solid-state battery.

[0028] The present invention has the following effects: the substrate (such as non-woven fabric) is surface-modified and grafted with a variety of active functional groups, such as -OH, -CO-, -COOH, -CO, and -NH2. These functional groups can polymerize with the unsaturated bonds (such as double bonds) on the binder in the electrolyte slurry to form a cross-linked network, enhance the chemical bonding between the substrate (such as non-woven fabric) and the slurry, and increase the roughness and shear strength of the surface of the substrate (such as non-woven fabric), thereby preparing a solid electrolyte membrane with a compact structure and not easy to drop. When the substrate is a non-woven fabric, the resulting solid electrolyte membrane is a chemically cross-linked flexible solid electrolyte membrane (such as a sulfide electrolyte membrane). Compared with traditional wet coating, the introduced surface-modified substrate (such as non-woven fabric) can enhance the interaction between the intermediate substrate layer and the molecules in the slurry, enhance the strength and structural stability of the electrolyte membrane, and do not use additional solvents to avoid affecting the stable structure of the electrolyte. In addition, the sheet or fiber mesh with a grid structure can reduce the electronic conductivity of the electrolyte membrane and effectively inhibit the self-discharge phenomenon. The independently formed electrolyte layer is easy to realize large-scale roll-to-roll production and can be used for high-energy-density solid-state batteries. The performance of solid-state batteries and electrical devices based on the solid-state electrolyte membrane (such as the chemically cross-linked sulfide solid-state electrolyte membrane) provided by the present invention is also improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the technical solution of the present invention, the following is a brief introduction to the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 This is one of the structural schematic diagrams of the solid electrolyte membrane according to the present invention.

[0031] Reference numerals: 1: first electrolyte layer, 2: second electrolyte layer, 3: nonwoven membrane, 4: fiber, 5: cross-linked network formed by polymerization. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1 This embodiment provides a solid electrolyte membrane, specifically a flexible sulfide electrolyte membrane, such as Figure 1As shown, it includes a first electrolyte layer 1, a second electrolyte layer 2 and a non-woven membrane 3 (specifically a PEVA membrane), the non-woven membrane 3 includes fibers 4, and the surface of the non-woven membrane 3 is connected through a cross-linked network 5 formed by polymerization with a binder.

[0034] The electrolyte membrane provided in this embodiment has the following preparation process: Substrate modification treatment: The 8-micron PEVA film was surface treated by glow discharge low-temperature plasma, with N2 as the discharge gas, a discharge pressure of 2000 Pa, a discharge power of 45 W, and a treatment time of 5 min to obtain a surface amino-modified PEVA film.

[0035] Prepare a certain proportion of sulfide electrolyte slurry: weigh 1.96g of lithium phosphorus sulfur chloride (LPSCl, i.e. Li6PS5Cl) electrolyte powder (powder size is 2μm), add 0.04g SBS and 2g toluene solution, and mix in a double planetary mixer for half an hour to obtain a slurry.

[0036] Electrolyte slurry coating: Pour part of the electrolyte slurry on the inside of the scraper with a scraper gap of 40μm, apply part of the electrolyte slurry on the aluminum foil, place it in a drying room for a period of time after coating, keep the ambient dew point temperature at -50℃ to -60℃, and place it for 15min to obtain the first electrolyte layer 1. Then place the surface amino PEVA membrane (i.e. non-woven fabric 3) on the semi-dry slurry layer, place it in a drying room for a period of time, keep the ambient dew point temperature at -50℃ to -60℃, and place it for 45min. Among them, the fibers 4 inside the PEVA membrane are random PEVA fibers with a porosity of 75%.

[0037] The remaining electrolyte slurry was poured onto the upper layer of the aminated PEVA film and the inner side of the scraper with a scraper gap of 80 μm, and the remaining electrolyte slurry was coated on the surface aminated PEVA film to obtain the second electrolyte layer 2. After coating, it was transferred to a 60° C. oven for 5 h to remove the toluene solvent.

[0038] Under an inert environment, after the solvent evaporates, the electrolyte membrane is pressed at 30°C and 10MPa for 1 minute to form a flexible, dense, structurally stable, and uniform chemically cross-linked flexible sulfide electrolyte membrane, where -NH2 on the surface of the PEVA membrane polymerizes with the unsaturated bonds of the binder to form a cross-linked network 5.

[0039] The preparation method of the sulfide electrolyte membrane of this embodiment uses a surface-modified non-woven fabric as a supporting layer to improve the flexibility of the sulfide electrolyte membrane. Chemical crosslinking is produced by the polymerization reaction between the active functional groups grafted on the surface of the modified non-woven fabric and the double bonds of the binder, which greatly enhances the strength and structural stability of the electrolyte membrane and improves the problems of weak mechanical properties and easy material loss of the wet-process electrolyte membrane. At the same time, the thickness of the electrolyte membrane is reduced, which is convenient for large-scale production and helps to further prepare high-energy density solid-state batteries. The non-woven fabric and sulfide solid electrolyte used are relatively stable, will not cause too much impact on ionic conductivity, and can reduce electronic conductivity, inhibit self-discharge, and improve capacity retention. At the same time, there is no need to introduce additional solvents to avoid affecting the stable structure of the electrolyte.

[0040] Example 2 This embodiment provides a solid electrolyte membrane, which is basically the same as the embodiment 1, except that during its preparation process, during the substrate modification process, the discharge power is 65 W and the treatment time is 5 min.

[0041] Example 3 This embodiment provides a solid electrolyte membrane, which is basically the same as the embodiment 1, except that during its preparation process, during the substrate modification process, the discharge power is 85 W and the treatment time is 5 min.

[0042] Example 4 This embodiment provides a solid electrolyte membrane, which is basically the same as the embodiment 1, except that during its preparation process, during the substrate modification process, the discharge power is 65 W and the treatment time is 8 min.

[0043] Example 5 This embodiment provides a solid electrolyte membrane, which is basically the same as the embodiment 1, except that during its preparation process, during the substrate modification process, the discharge power is 65 W and the treatment time is 11 min.

[0044] Example 6 This embodiment provides a solid electrolyte membrane, which is basically the same as the embodiment 4, except that PVC is used instead of PEVA in the process of substrate modification during its preparation, wherein the porosity of PVC is 75% and the thickness is 8 μm.

[0045] Example 7 This embodiment provides a solid electrolyte membrane, which is basically the same as the embodiment 4, except that the electrolyte slurry is coated in a different way during its preparation: the surface amino PEVA film is placed on the coating machine, the slurry is poured on the inner side of the scraper, the scraper gap is 80 microns, and after coating, it is transferred to a 60°C oven for 5 hours to remove the toluene solvent; in an inert environment, after the solvent evaporates, the electrolyte membrane is pressed at 30°C and 10MPa pressure for 1 minute. A flexible, dense, structurally stable, and uniform electrolyte membrane is formed.

[0046] Example 8 This embodiment provides a solid electrolyte membrane, which is basically the same as that of Embodiment 4, except that, during its preparation, the amount of SBS used is 0.02 g (1%).

[0047] Example 9 This embodiment provides a solid electrolyte membrane, which is basically the same as that of Embodiment 4, except that, during its preparation, the amount of SBS used is 0.10 g (5%).

[0048] Example 10 This embodiment provides a solid electrolyte membrane, which is basically the same as Embodiment 4, except that the porosity of the PEVA membrane is 80% and the thickness is 10 microns.

[0049] Comparative Example 1 This comparative example provides a solid electrolyte membrane, which is basically the same as Example 4, except that, during its preparation, a wet film forming method is adopted without an additional internal support structure: the electrolyte slurry is poured on the inside of a scraper with a scraper gap of 80 microns, and the electrolyte slurry is directly coated on an aluminum foil; after coating, it is transferred to a 60°C oven for 5 hours to remove the toluene solvent; under an inert environment, after the solvent evaporates, the above-mentioned electrolyte membrane is pressed at 30°C and a pressure of 10 MPa for 1 minute to form a solid electrolyte membrane.

[0050] Comparative Example 2 This comparative example provides a solid electrolyte membrane, which is basically the same as Example 4, except that an unmodified PEVA membrane is used in its preparation process.

[0051] Test example Test object: The solid electrolyte membranes described in Examples 1-10 and Comparative Examples 1-2 were used.

[0052] Test method: (1) Peel strength: tested using a tensile tester; (2) Tensile strength: tested using a tensile tester; (3) Electrochemical properties (electronic conductivity, first cycle efficiency of charge and discharge, and capacity retention rate after 100 cycles): The solid electrolyte membrane, ternary NCM811 positive electrode, and silicon oxide negative electrode were assembled into a solid-state soft-pack battery, and the long-term cycle stability was tested at 0.1C.

[0053] Test results: The test results are shown in Table 1 below.

[0054] Table 1 Among them, the wet-coated electrolyte membrane is prone to cracks and breakage, and the mechanical properties (peeling, stretching) cannot be tested by machine.

[0055] It can be seen from the experimental results in Table 1 that the solid electrolyte membrane prepared by the preparation method of the present invention is applied to solid-state soft-pack batteries, which can improve the first-week efficiency and the capacity retention rate after 100 cycles. Among them, the performance improvement of Example 4 is the most obvious, with the first-week efficiency reaching 79.1% and the capacity retention rate after 100 cycles reaching 90.1%.

[0056] By comparing the peel strength data of Comparative Example 2 and Example 4, it can be seen that under the same other conditions, grafting active functional groups on the surface of the non-woven fabric can achieve better results: high peel strength and more stability; by comparing the peel strength data of Example 7 and Example 4, it can be seen that under the same other conditions, the use of layered coating of the electrolyte slurry can achieve better results than directly coating the electrolyte slurry at one time: high peel strength; and the position of the non-woven fabric in the electrolyte layer can also be controlled, providing a basis for more possible applications.

[0057] The above embodiments are only used to demonstrate the preferred embodiments of the present invention. For the sake of brevity, other embodiments and combinations of the present invention, such as the surface modification treatment method, the selection of electrolyte materials and powder size, the selection of non-woven fabric types and their internal fiber arrangement methods, the selection of binder types, the types of solvents in the electrolyte slurry and the types of substrates, etc., are not described here in detail.

[0058] For example, with respect to substrates, as long as the substrates can be surface-modified to graft the above-mentioned active functional groups on the surface, such as non-woven fabrics or ceramic substrates, the inventive concept of the electrolyte membrane preparation method of the present invention can be adopted to modify the surface of the substrate to graft active functional groups for the preparation of solid electrolyte membranes. Therefore, the non-woven fabrics listed in the present invention are only one embodiment for preparing flexible solid electrolyte membranes, and the present invention does not list other substrates one by one.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A solid electrolyte membrane, characterized in that: The invention comprises an electrolyte layer and a substrate layer, wherein the electrolyte layer comprises a solid electrolyte material and a binder, and the substrate layer is surface-modified and grafted with at least one active functional group, wherein the active functional group can polymerize with the binder to form a cross-linked network; The binder is an unsaturated binder.

2. The solid electrolyte membrane according to claim 1, characterized in that: The active functional group includes at least one of -OH, -CO-, -COOH, -CO, and -NH2; And / or, the binder is selected from at least one of butadiene rubber, styrene-butadiene rubber, nitrile rubber, and styrene-butadiene-styrene block copolymer; And / or, the amount of the binder added is 1-10wt% of the amount of the electrolyte material used, preferably 1-5wt%.

3. The solid electrolyte membrane according to claim 1 or 2, characterized in that: The surface modification treatment is selected from at least one of plasma treatment, ozone treatment, chemical reagent oxidation, high energy radiation treatment, and corona discharge treatment; Preferably, the surface modification treatment is selected from plasma treatment and / or ozone treatment.

4. The solid electrolyte membrane according to any one of claims 1 to 3, characterized in that: The electrolyte layer comprises a first electrolyte layer and a second electrolyte layer, and the substrate layer is located between the first electrolyte layer and the second electrolyte layer or close to the electrode side.

5. The solid electrolyte membrane according to any one of claims 1 to 4, characterized in that: The substrate layer is selected from at least one of ceramic and non-woven fabric; Preferably, the nonwoven fabric is selected from one or two or more of polypropylene, polyester, nylon, acrylic, polyethylene-vinyl acetate, ethylene and vinyl; Preferably, the nonwoven fabric is selected from one or two or more of polyester, nylon, polyethylene-vinyl acetate and vinyl; Preferably, the nonwoven fabric comprises nonwoven fabric fibers, and the nonwoven fabric fibers are distributed in an irregular manner; Preferably, the nonwoven fabric fibers include at least one of meltblown nonwoven fabric fibers, cross-woven nonwoven fabric fibers, random nonwoven fabric fibers, spun nonwoven fabric fibers, needle-punched nonwoven fabric fibers, ruptured fiber nonwoven fabric fibers, and tow open fiber nonwoven fabric fibers; Preferably, the non-woven fabric fibers form a network structure; Preferably, the network structure is selected from at least one of a web of fibers formed into a sheet by friction, entanglement or bonding; Preferably, the porosity of the sheet or web is 35%-95%; Preferably, the porosity of the sheet or web is 75%-80%; Preferably, the sheet or web is parallel to the electrolyte layer; Preferably, the thickness of the nonwoven fabric is 5 μm-100 μm; Preferably, the nonwoven fabric has a thickness of 8 μm-16 μm.

6. The solid electrolyte membrane according to any one of claims 1 to 5, characterized in that: The solid electrolyte material is selected from at least one of an oxide electrolyte, a polymer electrolyte and a sulfide electrolyte; Preferably, the sulfide electrolyte is selected from Li2S-P2S5, Li 10 GeP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5I, Li6PS5Br and Li 5.5 PS 4.5 C l1.5 One or two or more of the following; Preferably, the powder particle size of the sulfide electrolyte is 1-10 μm; Preferably, the powder particle size of the sulfide electrolyte is 1-3 μm; Preferably, the electrolyte layer preparation process also includes a solvent; Preferably, the solvent is selected from one or more of toluene, xylene, anisole, butyl butyrate, n-heptane, pentane, hexane, octane, cyclohexane, cyclohexanone, toluene cyclohexanone, chlorobenzene, dichlorobenzene, dichloromethane, methanol, ethanol, isopropanol, ether, propylene oxide, methyl acetate, ethyl acetate, propyl acetate, acetone, methyl butyl ketone, methyl isobutyl ketone, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, and acetonitrile; Preferably, the solvent is selected from one or two or more of toluene, xylene, anisole and n-heptane.

7. The method for preparing a solid electrolyte membrane according to any one of claims 1 to 6, characterized in that: include: Subjecting the substrate to surface modification to obtain a surface-modified substrate; Preparing an electrolyte slurry and coating the electrolyte slurry.

8. The method for preparing the solid electrolyte membrane according to claim 7, characterized in that: When coating the electrolyte slurry, a layered coating method is adopted: first, a portion of the electrolyte slurry is coated on the current collector or PET film and preliminarily dried to obtain a first electrolyte layer, then a layer of the substrate is placed on the first electrolyte layer, and then the remaining slurry is coated on the substrate and dried to obtain the solid electrolyte membrane; Preferably, the substrate is placed when the first electrolyte layer is not completely dry.

9. A solid-state battery, characterized in that: It comprises the solid electrolyte membrane according to any one of claims 1 to 6 and / or the solid electrolyte membrane obtained by the preparation method according to claim 7 or 8.

10. An electrical device, characterized in that: Including the solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • Solid electrolyte composite membrane as well as preparation method and application thereof

    CN115020801A

  • Battery diaphragm, preparation method thereof and lithium battery

    CN115528380A

  • Light Emitting Device with Improved Light Output and Manufacturing Method thereof

    KR102760151B1

Cited By

  • Solid-state electrolyte membrane, preparation method thereof and solid-state battery

    CN121688091A